2014
DOI: 10.1016/j.jcin.2013.10.017
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Outcome in the COURAGE Trial (Clinical Outcomes Utilizing Revascularization and Aggressive Drug Evaluation)

Abstract: In a cohort of patients treated with OMT, anatomic burden was a consistent predictor of death, MI, and NSTE-ACS, whereas ischemic burden was not. Importantly, neither determination, even in combination, identified a patient profile benefiting preferentially from an invasive therapeutic strategy. (Clinical Outcomes Utilizing Revascularization and Aggressive Drug Evaluation [COURAGE]; NCT00007657).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
84
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 190 publications
(93 citation statements)
references
References 18 publications
5
84
0
4
Order By: Relevance
“…However, this post hoc analysis of a relatively small subgroup of the total cohort may have been confounded by the effect of two different anti-ischemic treatment strategies. 19 There has been considerable interest in recent years concerning clinical importance of CCR vs ICR in multivessel coronary artery disease. Most studies were angiographic observational or registry studies and used coronary anatomy as the benchmark.…”
Section: Discussionmentioning
confidence: 99%
“…However, this post hoc analysis of a relatively small subgroup of the total cohort may have been confounded by the effect of two different anti-ischemic treatment strategies. 19 There has been considerable interest in recent years concerning clinical importance of CCR vs ICR in multivessel coronary artery disease. Most studies were angiographic observational or registry studies and used coronary anatomy as the benchmark.…”
Section: Discussionmentioning
confidence: 99%
“…27 The odds ratio for prediction of acute events was 1.01 (95% confidence interval, 0.98-1.03; P=0.54) for ischemic burden versus 1.05 (95% confidence interval, 1.02-1.08; P=0.002) for atherosclerotic burden by quantitative coronary angiography. In addition to demonstrating the superiority of CTA over functional testing in identifying >50% diameter stenosis (DS), the randomized controlled trials are suggestive of the beneficial effect on prognostic outcomes of CTA versus functional testing-guided management.…”
Section: Why We Need Ct-ffrmentioning
confidence: 90%
“…The study demonstrated the safety of medical therapy for functionally nonsignificant lesions because the event-free survival rate at 2 years was similar between the 2 groups (89% versus 83% for the deferral versus performance groups, respectively; P=0. 27), as was the degree of angina. This cohort has now been followed for 15 years with no significant increase in revascularization rate in the deferral patients and a significantly lower rate of myocardial infarction (2.2 versus 10%, P=0.03).…”
mentioning
confidence: 99%
“…The burden of anatomic coronary atherosclerosis, whether obstructive or nonobstructive, is likely to be associated with more subclinical atherosclerotic lesions that may rupture and cause an adverse clinical outcome. 2,3 In patients with ST-elevation acute myocardial infarction and multivessel disease who undergo primary percutaneous coronary intervention of the culprit artery, quantification of the remaining coronary artery disease by the residual SYNTAX score may help to identify patients who are at increased risk for adverse events. 4 Indeed, in our population, the residual SYNTAX score was an independent predictor of major acute cardiovascular events and all-cause mortality during follow-up; these data have been submitted for publication.…”
Section: To the Editormentioning
confidence: 99%